Understanding pain : an introduction for patients and caregivers - Ali, Naheed, 1981-; Lewis, Moshe, 1968- (Rowman and Littlefield, 2015)
Pain is informally defined as the body's way of uncovering a problem. Whether due to an injury, infection, or something else, pain alerts a person that something is not right. Sometimes pain goes along with inflammation and swelling, and when it does, the problem is more evident. Oftentimes, pain is more generalized to the entire body, signaling a viral infection such as a flu virus. Still other times, there is no apparent root cause for a person's pain. Yet, millions of people suffer from some form of pain on a daily basis. Understanding Pain walks readers through the various types of pain, t.